Effect of propolis product on digestibility and ruminal parameters in buffaloes consuming a forage-based diet - Eduardo M. da Paula; Rafael B. Samensari; Fabiano L. Simioni; Maribel V. Valero; Lucimar P.P. de Moura; Selma L. Franco; Lucia M. Zeoula; João Batista G. Costa Jr. (Italian Journal of Animal Science, 2012)
This study evaluated the Propolis product (LLOS) effects on feed intake, dry matter (DM) and nutrients total digestibility, rumen characteristics and microbial efficiency in buffaloes fed a roughage based diet (70% Cynodon spp hay and 30% concentrate). Using a 4¥4 latin square design, four crossbred buffalo (Murrah x Jafarabadi) steers (519.0±13.0 kg body weight - BW), were fed four treatments with three LLOS concentrations: Control (no LLOS), LLOS B3+ (0.272 mg/g flavonoid chrysin equivalents), LLOS C1 (0.092 mg/g flavonoid chrysin equivalents), and LLOS C1+ (0.184 mg/g flavonoid chrysin equivalents). Diet formulation was 60% total digestible nutrient (TDN) and 11% crude protein (CP). No difference was observed in DM intake among experimental diets (P>0.05). Steers fed LLOS C1 had greater (P<0.05) coefficients of digestibility for DM (67.2 vs 62.7%), organic matter (OM) (68.1 vs 63.7%), neutral detergent fibre (NDF) (61.7 vs 56.6%), total carbohydrates (TCHO) (67.7 vs 63.2%) and TDN (66.1 vs 62.8%) compared to animals fed the control diet. LLOS C1 provided greatest (P<0.05) short chain fatty acids (SCFA) production (141.89 vs 129.15 μM/mL) and butyric production (16.15 vs 14.05 μM/mL) compared to control. The lowest rumen pH (6.65; P<0.05) was observed in steers fed diets with LLOS C1. No difference (P>0.05) was observed for ammoniacal nitrogen (N-NH3), solid and liquid passage rate and microbial efficiency among treatments. In this study LLOS C1 improved forage diet efficiency in buffalo steers.